PERAN DAN TANGGUNG JAWAB PT. JASA RAHARJA (PERSERO) DALAM MEMBERIKAN SANTUNAN ASURANSI TERHADAP KORBAN KECELAKAAN LALU LINTAS JALAN (Studi Pada PT. Jasa Raharja (Persero) Cabang Rantauprapat) - FAHRUL ROZY (JURNAL CIVIL LAW USU, 2013)
Abstrak : Transportation has a very broad role and importance for the economic development of the nation. Developments in science and technology especially in the field of traffic and transportation, it not only provides benefits and positive influence on the behavior of people's lives, but it can also have negative impacts, such as the emergence of problems in areas such as traffic accidents. The government through the Law. 34 Year 1964 on Road Traffic Accident Fund provides insurance benefits for victims of traffic accidents, which in this implementation is left to the PT. Jasa Raharja (Persero). Duties and responsibilities are to collect funds from the public through donations compulsory motor vehicle owners are performed each year, and thereafter is channeled back to the community through the insurance compensation to the victim or the victim's heirs, which aim to reduce the burden of costs due to road traffic accidents, which given the amount of compensation has been set in the Regulation of the Minister of Finance Decree No. 36/PMK.010/2008 of Great Benefit and Contribution Compulsory Road Traffic Accident Fund. Keywords: Roles and Responsibilities, Road Traffic Accidents,